The narrow mesh: A new shaped mesh for the treatment of inguinal hernia - Enrico Nicolo (Journal of Surgery and Surgical Research - Peertechz Publications, 2020)
The present communication relates to inguinal hernia repair, and more particularly to a preshaped inguinal hernia prosthetic material, polypropylene, 6×2.5 centimeters in size, (Figure 1) that has a lateral semicircular non-encircling cord locating structure in order to protect the spermatic cord and that it is interposed between the conjoined tendon and the inguinal ligament in such a way as to repair the hernia and at the same time to reconstitute the physiology of the inguinal canal.